MicroRNA‐155 in oral squamous cell carcinoma: Overexpression, localization, and prognostic potential. Issue 7 (27th June 2014) - Shi, Lin‐Jun; Zhang, Chen‐Yang; Zhou, Zeng‐Tong; Ma, Jing‐Yuan; Liu, Yang; Bao, Zhe‐Xuan; Jiang, Wei‐Wen
ABSTRACT Background Oral squamous cell carcinoma (OSCC) is a common malignancy with poor prognosis. MicroRNAs (miRNAs) play an important role in cancer, but their role in OSCC is not clarified. Methods We performed miRNA microarray, quantitative reverse transcription polymerase chain reaction (qRT‐PCR), and fluorescence in situ hybridization (FISH) to examine miRNA expression in OSCC and paired adjacent cancer‐free mucosal (ACF) tissues. Results Thirteen miRNAs, including miRNA‐155, were upregulated (>2‐fold) in OSCC against ACF. MiRNA‐155 was confirmed to have significantly higher expression in OSCC against ACF (paired‐samples t test; p = .041) and it was localized in the cancer nest, inflammatory area, and vascular endothelium of OSCC. High expression of miRNA‐155 in ACF tissue was an independent prognostic indicator for OSCC survival. Conclusion MiRNA‐155 was overexpressed in OSCC and it was located in the cancer nest, inflammatory area, and vascular endothelium of OSCC. High miRNA‐155 expression level in ACF may predict poor prognosis in patients with OSCC. © 2014 Wiley Periodicals, Inc. Head Neck 37: 970–976, 2015